Design and Development of Variable Rate Metering System for Fertilizer Application - Gurjar, Bholuram; Sahoo, P. K.; Kumar, Adarsh (Journal of Agricultural Engineering, 2018)
A variable rate fertilizer metering mechanism was designed by changing the speed of the feed shaft for use in variable rate fertilizer applicator. A micro-controller unit programmed with a Pulse Width Modulation (PWM) motor driver was used to run the feed shaft for varying speeds. Two types of fluted rollers (straight and helical flute) were used with varying number of flutes having same volume for each fluted roller. No significant difference in discharge rate between helical and straight fluted roller was observed with varying number of flutes (6, 8, 10, and 12). However the discharge rate of SSP fertilizer was significantly higher than that for DAP. Also, significant difference was observed in applied torque and power requirement for straight and helical flute.